Early and late C‐peptide responses during oral glucose tolerance testing are oppositely predictive of type 1 diabetes in autoantibody‐positive individuals. Issue 6 (27th February 2020) - Ismail, Heba M.; Becker, Dorothy J.; Libman, Ingrid; Herold, Kevan C.; Redondo, Maria J.; Atkinson, Mark A.; Cleves, Mario A.; Palmer, Jerry; Sosenko, Jay
Abstract: We examined whether the timing of the C‐peptide response during an oral glucose tolerance test (OGTT) in relatives of patients with type 1 diabetes (T1D) is predictive of disease onset. We examined baseline 2‐h OGTTs from 670 relatives participating in the Diabetes Prevention Trial‐Type 1 (age: 13.8 ± 9.6 years; body mass index z‐score: 0.3 ± 1.1; 56% male) using univariate regression models. T1D risk increased with lower early C‐peptide responses (30–0 min) (χ 2 = 28.8, P < 0.001), and higher late C‐peptide responses (120–60 min) (χ 2 = 23.3, P < 0.001). When both responses were included in a proportional hazards model, they remained independently and oppositely associated with T1D, with a stronger overall association for the combined model than either response alone (χ 2 = 41.1; P < 0.001). Using receiver operating characteristic curve analysis, the combined early and late C‐peptide response was more accurately predictive of T1D than area under the curve C‐peptide ( P = 0.005). Our findings demonstrate that lower early and higher late C‐peptide responses serve as indicators of increased T1D risk.